The Legislative Requirement That Zoning and Land Use Controls Be Consistent with an Independently Adopted Local Comprehensive Plan: A Model Statute - Stuart Meck (Washington University Journal of Law & Policy, 2000)
This Essay critically reviews the history of the “in accordance with a comprehensive plan” language in the Standard State Zoning Enabling Act and its companion, the Standard City Planning Enabling Act, drafted by an advisory committee of the U.S. Department of Commerce in the 1920s. It then discusses contemporary consistency requirements in state planning and land use enabling statutes. Finally, it presents a model statute intended to clarify the relationship between the local comprehensive plan and various types of land use decisions and actions.
Keywords: City planning and redevelopment law; Land use; Zoning law